THE EFFICACY OF COGNITIVE THERAPY AND ACTIVITY PARTICIPATION ON REDUCING LEVEL OF DEPRESSION AMONG THE ELDERLY - Al-Absi, Bushara Jamil (Journal of Educational and Psychological Sciences, 2022)
This study aimed to evaluate the effectiveness of cognitive intervention program and activity participation in reducing level of depression among a sample of elderly persons. The sample of the study consisted of 30 elderly individuals scored high on Beck inventory for depression and divided randomly into three group: the first experimental group (cognitive therapy) of (10) persons, the second experimental group, (activity participation) of (10) persons, and the control group of (10) persons.Cognitive therapy was used with the first experimental group; and the activity participation with the second experimental group while the control group was not subjected to any program.The two programs lasted for three months at a rate of a weekly session for each program lasting for 60 minutes. Pre, post and follow up measures were obtained.The results showed that there were differences of statistical significance between the first experimental group (cognitive therapy) and the control group in post test and follow up، which means that the program depending on the cognitive therapy led to reducing depression level among the first experimental group individuals.The results showed differences of statistical significance between the second experimental group (activity participation) and the control group in post test and follow up، which means that the program depending on activity participation led to reducing level of depression among the individuals of the second experimental group.The results showed no statistical differences between the first and second experimental groups.
Keywords: cognitive therapy; participation in activities